2023
DOI: 10.3390/jcm12165356
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Residual Neoplasia after a Local-Risk Resection of Colorectal Lesions by Endoscopic Submucosal Dissection: A Multinational Study

João Santos-Antunes,
Mathieu Pioche,
Felipe Ramos-Zabala
et al.

Abstract: Endoscopic submucosal dissection (ESD) in colorectal lesions is demanding, and a significant rate of non-curative procedures is expected. We aimed to assess the rate of residual lesion after a piecemeal ESD resection, or after an en bloc resection but with positive horizontal margins (local-risk resection—LocRR), for colorectal benign neoplasia. A retrospective multicenter analysis of consecutive colorectal ESDs was performed. Patients with LocRR ESDs for the treatment of benign colorectal lesions with at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There are only a few studies on residual tumors after ESD. João Santos-Antunes et al reported that piecemeal resection, poorly differentiated tumors, and positive vertical margin were associated with residual tumors at the ESD site after analyzing 135 T1 CRCs using non-curative ESD 10 , 21 . Although our study did not include piecemeal resected cases, the result was inconsistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on residual tumors after ESD. João Santos-Antunes et al reported that piecemeal resection, poorly differentiated tumors, and positive vertical margin were associated with residual tumors at the ESD site after analyzing 135 T1 CRCs using non-curative ESD 10 , 21 . Although our study did not include piecemeal resected cases, the result was inconsistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%